Analisis Efektivitas Komunikasi Pemangku Kepentingan untuk Keberlanjutan Bisnis UMK di Geopark Pongkor - Baban Sarbana; Amiruddin Saleh; Anna Fatchiya; Muhammad Firdaus (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
Stakeholder collaboration has an important role in the sustainability of Micro and Small Enterprises (MSEs) businesses. Nature conservation and community welfare underlie geoproduct management in the Pongkor National Geopark Area. Collaborative communication in development communication requires the involvement of stakeholders in the development process from planning, implementation to monitoring and evaluation to realize MSEs business sustainability. The purpose of this research is to analyze the effectiveness of stakeholder communication in realizing MSE business sustainability in Pongkor National Geopark. The research was conducted in August-September 2022 in Bogor Regency. The results showed that collaborative communication between stakeholders was not optimal in MSEs business development programs. Such as the low participation of MSE actors in human resource quality improvement programs, the lack of collaboration between stakeholders through interactive media channels and the suboptimal utilization of government and business program facilitation in improving competitive products.